Caries Experience among Females aged 16–21 in Punjab, India and its Relationship with Lifestyle and Salivary HSP70 Levels - Kaur, Rabinder; Kataria, Hardeep; Kumar, Sushil; Kaur, Gurcharan (European Journal of Dentistry, 2010)
Objectives: The objective of the current study was to assess the prevalence and means of dental caries experience and the prevalence of calculus among college students and their awareness of general dental health. The correlation between the experience of caries and extracellular levels of heat shock protein-70 (eHSP70) was studied in saliva samples of these students to ascertain whether eHSP level changes as a result of increased caries experience of these subjects.Methods: The current study was conducted among 147 female undergraduate students aged 16– 21 in the state of Punjab, India. Dental examinations were performed to assess for the presence of calculus and DMFT, and subjects were asked to fill in a questionnaire. The data were recorded and analysed for the role of various factors in the prevalence of caries, including dietary habits. Saliva samples were collected for ELISA-based assay of eHSP70 levels.Results: The prevalence of caries experience (DMFT>0) was 63.2%, with average DMFT of 2.91 in students aged 16–18 and 3.26 in those aged 19–21. Of those with caries, 68% also showed the presence of calculus, compared with 60.0% of subjects with DMFT=0. The level of eHSP was significantly higher (P<.05) in subjects with higher levels of caries (DMFT=4–8) compared with subjects having DMFT between 0 and 3.Conclusions: A significant relationship was observed between caries experience and oral hygiene habits, emphasizing the need to design and plan preventive strategies for persons at greatest risk. The correlation between mean DMFT and prevalence of eHSP was highly significant. This is the first study to report a correlation between caries experience and the saliva level of stress response protein HSP70. (Eur J Dent 2010;4:308-313)
Keywords: Dental caries; HSPs; Dental health; DMFT; Calculus